1,3-Dibenzyl-2-methylbenzimidazolium chloride - Ennajih, H.; Bouhfid, R.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The cation of the title salt, C(22)H(21)N(2)(+)center dot Cl(-), contains a planar benzimidazolium unit (r.m.s. deviation = 0.02 A); the phenyl rings of the benzyl substituents form dihedral angles of 68.2 (1) and 79.7 (1)degrees with the plane of the benzimidazolium fragment.